RFID in payment systems: the implementation and ramifications - Zulkefli, Zulaikha; Anwar, Norizan; Salji, Mohd Rafiz; Kurniawan, Yohannes (Faculty of Information Management, 2025)
This research paper explores the implementation and impact of Radio Frequency Identification (RFID) technology in toll collection systems, emphasizing its role in enhancing payment efficiency and user experience. With the introduction of RFID lanes in toll plazas across Malaysia, the study examines the growth in RFID adoption, noting a significant increase in registered vehicles equipped with RFID tags from 1.55 million in 2021 to 2.36 million by the end of 2022. The paper reviews previous studies to establish a foundation for understanding consumer intentions and satisfaction with RFID payment systems, highlighting the importance of effective information policies to alleviate concerns and enhance acceptance. By analyzing the current landscape of contactless payment technologies, this study aims to provide insights for future research and policy development, ultimately contributing to the advancement of intelligent transportation systems.